2021
DOI: 10.3389/fimmu.2021.670566
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Adipose Tissue to the Chronic Immune Activation and Inflammation Associated With HIV Infection and Its Treatment

Abstract: White adipose tissue (AT) contributes significantly to inflammation – especially in the context of obesity. Several of AT’s intrinsic features favor its key role in local and systemic inflammation: (i) large distribution throughout the body, (ii) major endocrine activity, and (iii) presence of metabolic and immune cells in close proximity. In obesity, the concomitant pro-inflammatory signals produced by immune cells, adipocytes and adipose stem cells help to drive local inflammation in a vicious circle. Althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 208 publications
1
22
0
2
Order By: Relevance
“…Moreover, ACBP levels were only analyzed in plasma samples. The tissue expression of ACBP, notably in the liver and adipose tissue, should be compared in ECs vs. ART-naïve and ART-treated PLWH [ 42 ]. The comparatively low ACBP plasma levels of ECs could reflect a reduced secretion of ACBP, as well as a lower expression of intracellular ACBP.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ACBP levels were only analyzed in plasma samples. The tissue expression of ACBP, notably in the liver and adipose tissue, should be compared in ECs vs. ART-naïve and ART-treated PLWH [ 42 ]. The comparatively low ACBP plasma levels of ECs could reflect a reduced secretion of ACBP, as well as a lower expression of intracellular ACBP.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive ECM production in adipose tissue (i.e., fibrosis) is a characteristic of the unhealthy phenotype found in non-alcoholic steatohepatitis development, inflammatory conditions, insulin resistance, and breast cancer [10][11][12][13][14]. Recent evidence indicated that fibrosis is strongly associated with obesity, metabolic dysfunction, and difficulty in weight loss, suggesting that the ECM microenvironment may increase disease progression [6,9,15]. Presently, there is great concern in investigating approaches to attenuate the harmful effects of ECM enlargement.…”
Section: Introductionmentioning
confidence: 99%
“…Both HIV infection and ART modify the adipose tissue composition, distribution, and function [12,17]. The virus itself targets adipose tissue directly by infecting adipose tissue-resident cells (notably CD4 + T cells) and indirectly via viral protein release, activation of inflammation, and the immune system and gut disruption [18]. Furthermore, in obese PLHIV, adipose dysfunction is boosted by inflammation, which in turn is an outcome of excess adipose and obesity-induced metabolic disturbances.…”
Section: Introductionmentioning
confidence: 99%